Administrative Services at the Regional Secretariat of North Sulawesi Province - Franklin Timothy Aray; Evi Elvira Masengi; Thelma Wawointana (Technium Social Sciences Journal, 2025)
This research aims to analyze strategies to improve the quality of administrative services, identify inhibiting factors, and provide recommendations for solutions to support the realization of public services that are more responsive, accountable, and oriented to community needs. This research was conducted using a descriptive qualitative method based on the Miles and Huberman model. Data were collected through observation, in-depth interviews with key informants, and related documentation. The research location was in the Administrative Services Unit (ULA) of the General Bureau of the Regional Secretariat of North Sulawesi Province. Data analysis techniques included data reduction, data presentation, and conclusion drawing, with triangulation to ensure data validity. The results showed that despite improvements in the transparency and accountability aspects of the service, there were still obstacles in terms of service time, compliance with standard operating procedures (SOPs), and inadequate supporting facilities. The inhibiting factors include lack of human resource training, limited infrastructure, and bureaucratic complexity. In conclusion, improving the quality of administrative services at ULA can be achieved through strengthening employee capacity, providing adequate facilities, and optimizing the implementation of SOPs. This research recommends the need for continuous innovation and collaboration between stakeholders to create more inclusive and highly competitive services.